Molecular Cloning and Expression Analysis of Cu/Zn SOD Gene from Gynura bicolor DC. - Xin Xu; Zhi-fang Yu; Jing Kong; Mei-jun Yi; Chen Huan; Li Jiang (Journal of Chemistry)
Superoxide dismutase is an important antioxidant enzyme extensively existing in eukaryote, which scavenges reactive oxygen species (ROS) and plays an essential role in stress tolerance of higher plants. A full-length cDNA encoding Cu/Zn SOD was cloned from leaves of Gynura bicolor DC. by rapid amplification of cDNA ends (RACE). The full-length cDNA of Cu/Zn SOD is 924 bp and has a 681 bp open reading frame encoding 227 amino acids. Bioinformatics analysis revealed that belonged to the plant SOD super family. Cu/Zn SODs of the Helianthus annuus, Mikania micrantha, and Solidago canadensis var. scabra all have 86% similarity to the G. bicolor Cu/Zn SOD. Analysis of the expression of Cu/Zn SOD under different treatments revealed that Cu/Zn SOD was a stress-responsive gene, especially to 1-MCP. It indicates that the Cu/Zn SOD gene would be an important gene in the resistance to stresses and will be helpful in providing evidence for future research on underlying molecular mechanism and choosing proper postharvest treatments for G. bicolor.